Key Factors in Improving the Sustainable Performance of Urban Drinking Water Services - Agustin, Meilan; Moengin, Parwadi; Sari, Emelia; Rinanti, Astri; Abu, Mohd. Yazid (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Water is a basic element for human survival, yet although 71% of the Earth's surface consists of water, only 1% of it is accessible to humans. Climate change, urbanization, and environmental issues are challenges experienced by the efforts of drinking water services in urban areas. In addition to providing sufficient drinking water, drinking water services must also pay attention to energy use and carbon emissions. This study aims to determine the factors that impact the sustainable performance of drinking water services in urban areas. The research method was conducted using bibliometric analysis. The analysis was conducted on 50 reputable articles with a publication period of 2013-2023, with the keywords urban water and municipal water. According to previous research, the water supply system in urban areas can be divided into three sub-systems: raw water, water treatment, and distribution. If associated with sustainability, the factors can be divided into economic factors, such as affordability, continuity, and quantity. Environment: pollution and carbon emissions. Social: accessibility and customer behavior. Most previous studies have focused only on economic aspects, further studies are needed to integrate all these factors into a performance measurement system to help decision-makers align strategic targets into operation level activities.